Inhibition by Ethambutol of Mycolic Acid Transfer into the Cell Wall of Mycobacterium smegmatis - Takayama, Kuni (1979)
Ethambutol simultaneously inhibited the transfer (presumably via mycolyl acetyl trehalose) of mycolic acids into the cell wall and stimulated the synthesis of trehalose dimycolates of Mycobacterium smegmatis. Structural similarities of the drug and mycolyl acetyl trehalose suggested that competitive inhibition was involved.